A new genus and two new species of tripterygiid fishes from Costa Rica - Bussing, William A (1991)
The triplefm blenny, Axoclinus cocoensis, sp. nov. is described from 1307 specimens collected at numerous localities around Isla del Coco, Costa Rica. Another tripterygiid is described and placed in the genus Lepidonectes, gen. nov. Rosenblatt, clarkhubbsi, sp. nov. The latter is described from 379 specimens collected along the entire Pacific coastline of Costa Rica; the species is also known from westem Panama and possibly has a larger distribution in Central America.